2021
DOI: 10.1590/1414-431x2021e11439
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of cathepsin Z mRNA expressed by immune blood cells: diagnostic and prognostic implications in prostate cancer

Abstract: Cathepsin Z (CTSZ) is a cysteine protease responsible for the adhesion and migration of both immune and tumor cells. Due to its dual role, we hypothesized that the site of CTSZ expression could be determinant of the pro- or anti-tumorigenic effects of this enzyme. To test this hypothesis, we analyzed CTSZ expression data in healthy and tumor tissues by bioinformatics and evaluated the expression levels of CTSZ mRNA in the blood cells of prostate cancer (PCa) patients by qRT-PCR compared with healthy subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Compared with the sham group, the expression of complement C3 in the HI group was signi cantly increased, indicating that complement pathway components accumulate in the HI group and that GSS treatment can signi cantly reduce the expression of complement C3 (Figure 5A, B), which is consistent with the RNA-Seq results (Figure 5E). Cathepsin Z (CTSZ) is a member of the cysteine cathepsin family, is a lysosomal cysteine proteinase and has exopeptidase activity [24]. The results showed that CTSZ expression was increased after HIE and that GSS treatment inhibited the increased expression of this protein (Figure 5A, C).…”
Section: Validation Of the Rna-seq Results By Western Blottingmentioning
confidence: 99%
“…Compared with the sham group, the expression of complement C3 in the HI group was signi cantly increased, indicating that complement pathway components accumulate in the HI group and that GSS treatment can signi cantly reduce the expression of complement C3 (Figure 5A, B), which is consistent with the RNA-Seq results (Figure 5E). Cathepsin Z (CTSZ) is a member of the cysteine cathepsin family, is a lysosomal cysteine proteinase and has exopeptidase activity [24]. The results showed that CTSZ expression was increased after HIE and that GSS treatment inhibited the increased expression of this protein (Figure 5A, C).…”
Section: Validation Of the Rna-seq Results By Western Blottingmentioning
confidence: 99%
“…5E ). Cathepsin Z (CTSZ) is a member of the cysteine cathepsin family, is a lysosomal cysteine proteinase, and has exopeptidase activity [ 29 ]. The results showed that CTSZ expression was increased after HIE and that GSS treatment inhibited the increased expression of this protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Research speci cally focusing on the impact of cathepsin S on HCC risk has been sparse, highlighting the need for further detailed functional studies to elucidate its role in HCC progression. Additionally, insights from reverse MR analysis have illuminated an increase in cathepsin Z expression due to HCC, providing an explanation for the elevated cathepsin Z levels previously observed in HCC patients [37,38].…”
Section: Discussionmentioning
confidence: 99%